Entrepreneurial Intention Among Students: The Role of Entrepreneurial Education, Self-Efficacy, and Network - Kwetan, Aditya Kristianto; Harjanti, Dhyah (Profesional Muda Cendekia Publishing, 2024)
Research Aims: Indonesia has enormous natural resources. This wealth of natural resources has the potential to become a business opportunity and give birth to new entrepreneurs. This study aimed to identify the effect of entrepreneurial education, self-efficacy, and network on entrepreneurial intention. Design/methodology/approach: The method of research used in this study was quantitative. The number of samples used was 91 college students domiciled in Eastern Indonesia (EI). The sampling technique used in this study was the purposive sampling technique. The data analysis technique used was descriptive statistics with the Partial Least Square program (PLS). The majority of the respondents in this study were male (53%), 20 years old (52.7%), majoring in economics and business (60.4%), and currently in their third year of college (58.2%). Research Findings: The results showed that entrepreneurial education had a positive and significant effect on self-efficacy, and entrepreneurial education, self-efficacy, and the network had a positive and significant effect on entrepreneurial intention. Theoretical Contribution/Originality: The findings of this research can be used as an evaluation of the results of various efforts made to encourage the growth of entrepreneurial intentions through the provision of educational facilities and networks in Eastern Indonesia.